2013
DOI: 10.3390/molecules180910721
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effects of Ixora parviflora Extract against Exhaustive Exercise-Induced Oxidative Stress in Mice

Abstract: Ixora parviflora, a species of the Rubiaceae, is rich in polyphenols and flavonoids, and has been traditionally used as a folk medicine. An I. parviflora extract (IPE) has great antioxidant activity in vitro, including a scavenging effect on superoxide radicals, reducing power, and ferrous ion-chelating ability. However, whether IPE is efficacious against oxidative damage in vivo is not known. The purpose of this study was to determine the protective effects of IPE treatment on hepatic oxidative stress and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 25 publications
0
25
0
2
Order By: Relevance
“…It was proven that intense exercises resulted in increasing oxygen consumption, and caused oxidative stress as an additional result of increased reactive oxygen species production . Exogenous antioxidants are capable of preventing oxidative damage.…”
Section: Tyrosol and Salidrosidementioning
confidence: 99%
“…It was proven that intense exercises resulted in increasing oxygen consumption, and caused oxidative stress as an additional result of increased reactive oxygen species production . Exogenous antioxidants are capable of preventing oxidative damage.…”
Section: Tyrosol and Salidrosidementioning
confidence: 99%
“…In a previous study conducted by Kan, et al, 29 it was found that the GPx activity was significantly increased with the supplementation of flavonoids after performing an exhaustive swimming exercise in mice. Tauler, et al, 30 also found that GPx activities were significantly increased after taking antioxidant diet supplementation combined with exercise training in amateur trained male athletes.…”
Section: Discussionmentioning
confidence: 89%
“…Several previous studies showed different finding with the present finding. For instance, Kan, et al, 29 found that SOD activity level was significantly increased with supplementation of polyphenols and flavonoids rich which is Ixora parviflora extract after an exhaustive swimming in mice. Miyazaki, et al, 26 also found that SOD activity was significantly increased after 12 weeks of intense training in young males.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that excessive production of free radicals can reduce the levels of antioxidant-associated enzymes and can lead to cell and tissue injury [28]. To mitigate the cumulative burden of oxidative stress and to attenuate the deleterious effects of ROS, cells generally utilise antioxidant defences and scavenge ROS and MDA.…”
Section: Discussionmentioning
confidence: 99%